2020
DOI: 10.1016/j.molmet.2020.101054
|View full text |Cite
|
Sign up to set email alerts
|

Disabling MNK protein kinases promotes oxidative metabolism and protects against diet-induced obesity

Abstract: Objectives Diet-driven obesity is increasingly widespread. Its consequences pose major challenges to human health and health care systems. There are MAP kinase-interacting kinases (MNKs) in mice, MNK1 and MNK2. Studies have demonstrated that mice lacking either MNK1 or MNK2 were partially protected against high-fat diet (HFD)-induced weight gain and insulin resistance. The aims of this study were to evaluate the phenotype of mice lacking both MNKs when given an HFD, to assess whether pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Nevertheless, treatments with ACA, Rapa or 17eE2 do not seem to affect any of the MAPK/ERK pathway protein levels, including MNK or eIF4E levels, in contrast to the upregulation of 4EBP1 protein [ 8 ] induced by these drugs. Recently it has been reported that reduction in MNK activity and the consequential decline in phosphorylation eIF4E improve glucose homeostasis [ 63 ], suggesting that some of the beneficial effects of these drugs and anti-aging genes may be under the control of the MAPK/ERK/eIF4E pathway. In addition, a reduction in the phosphorylation status of eIF4E (peIF4E) can upregulate the translation of a unique set of mRNAs [ 64 , 65 ], suggesting that some of the effects seen in previously published data in the upregulation of CIT proteins [ 8 ] by ACA, Rapa and 17aE2 could be, in part, the result of regulation of the MAPK/ERK/eIF4E signaling by the treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, treatments with ACA, Rapa or 17eE2 do not seem to affect any of the MAPK/ERK pathway protein levels, including MNK or eIF4E levels, in contrast to the upregulation of 4EBP1 protein [ 8 ] induced by these drugs. Recently it has been reported that reduction in MNK activity and the consequential decline in phosphorylation eIF4E improve glucose homeostasis [ 63 ], suggesting that some of the beneficial effects of these drugs and anti-aging genes may be under the control of the MAPK/ERK/eIF4E pathway. In addition, a reduction in the phosphorylation status of eIF4E (peIF4E) can upregulate the translation of a unique set of mRNAs [ 64 , 65 ], suggesting that some of the effects seen in previously published data in the upregulation of CIT proteins [ 8 ] by ACA, Rapa and 17aE2 could be, in part, the result of regulation of the MAPK/ERK/eIF4E signaling by the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a reduction in the phosphorylation status of eIF4E (peIF4E) can upregulate the translation of a unique set of mRNAs [ 64 , 65 ], suggesting that some of the effects seen in previously published data in the upregulation of CIT proteins [ 8 ] by ACA, Rapa and 17aE2 could be, in part, the result of regulation of the MAPK/ERK/eIF4E signaling by the treatments. However, a direct test of this hypothesis would require using the intervention protocols in the knockout model of the MAPK/ERK signaling, such is the MNK-KO mice [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, substances that eliminate its presence effectively reduce the proliferation of tumor cells. This seems to be particularly true, as simultaneous inhibition of Mnk1/2 leads to a switch to oxidative metabolism [ 67 ], which is associated with ROS production in cancer cells.…”
Section: Synthetic Retinoidsmentioning
confidence: 99%
“…Overexpression of eIF4E, p-eIF4E and MNKs has been found in various cancers [ 10 , 11 , 12 , 13 ], promoting cell proliferation, inducing cell migration and invasion, and regulating tumor microenvironment (TME) by increasing the secretion of proinflammatory cytokines [ 14 , 15 ]. Additionally, MNKs could prevent weight gain and enhance insulin sensitivity and energy expenditure in a high=fat diet [ 16 , 17 , 18 ]. Moreover, inhibition of MNKs impaired the Toll-like receptor (TLR) signaling pathways [ 15 ], cellular Type I and Type II interferon signaling [ 19 , 20 ], and decreased the production of IL-6, IL-10, MCP-1, etc.…”
Section: Introductionmentioning
confidence: 99%